PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (Numbered Head Together) UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VII A SMP NEGERI 3 BANGKO TAHUN PELAJARAN 2015/2016 - Hermanto '; Arnentis '; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Teachers as implementers in all schools are required to constantly improve its ability in mastering and convey the subject matter. This is intended so that student learning outcomes can be improved. One of the ways to improve student learning results is to use the cooperative learning model of NHT. Research is conducted to improve learning outcomes through the implementation of IPA model Cooperative Learning Type NHT On Grade VII A SMP Negeri 3 Bangko Years Lessons 2015/2016. This research was carried out in junior high the land Even Semester Bangko 3 Years Lessons 2015/2016 in February up to March 2016. This research is a research Action class (PTK) which consists of two cycles. The subject of research that is grade VII A of 24 people consisting of 14 male students and 10 female students. The data collected in this research is the result of student learning that consists of absorption, learning and recognition of the group as well as the student's activities and the activities of the teacher. Instruments data using tests and observation sheets. The results showed the results of students consisting of absorbance, ketuntasan learning, group learning activities, awards the student and teacher experience increased activity. Absorption cycle I is 75.33% (enough) and cycle II increased to 80.70% (good). Study on cycle I is 90.48% (category has been completed) and on cycle II increased to 100.00% (category has been completed). Group Award at the cycle I i.e. 1 group of award winning super group 3 and get great rewards. Just as in cycle II, i.e. 1 group was awarded the super and 3 groups awarded excellent. Student activity on the cycle I is 86.10% (good) and cycle II increased to 94% (excellent). The activity of the teacher in the cycle I is 91.18% (excellent) and cycle II increased to 100.00% (excellent). It can be concluded that the application of the cooperative learning model of application type NHT can improve learning outcomes IPA grade VII A SMP Negeri 3 Bangko Year 2015/2016 Lessons.Keywords: cooperative NHT, learning results, IPA2